KEBIASAAN KONSUMSI MINUMAN DAN ASUPAN CAIRAN PADA ANAK USIA SEKOLAH DI PERKOTAAN - Dodik Briawan; Paramitha Rachma; Kartika Annisa (Jurnal Gizi dan Pangan, 2011)
The study objectives were to analyze the food and beverages contribution to the total fluid intake, and the sign of mild dehydration of school age children. The cross-sectional study was applied to 78 boys and 78 girls of elementary school students in Bogor City. Two days food recall was applied to estimate fluid intake. The fluid intake was a summation of various food and beverages. The result showed beside of plain water, most of the school children used to consumed milk and tea (>70%) at home. The total fluid intake was 2283 mL for boys and 2024 mL for girls, and its contribution was 21 percent from food (430-490 mL) and 78 percent from beverages (1600-1800 mL). There are 67.4 percent boys and 62.8 percent girls suffered mild dehydration with minimum three physical signs of dehydration. There are still 18.6 percent boys and 3.5 percent girls that their fluid intake below 100% of the requirement.